2020
DOI: 10.1002/jcla.23652
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)‐dependent steroid dehydrogenase‐like protein and neutral cholesterol ester hydrolase 1 serve as novel markers for early detection of gastric cancer identified using quantitative proteomics

Abstract: Background Gastric cancer (GC) is the third most common cause of cancer deaths worldwide. In the present study, we aimed to identify novel GC biomarkers by integrating isobaric tags of relative and absolute quantitation (iTRAQ) for aberrantly expressed proteins in GC patients. Methods Using stable isotope tags, we labeled an initial discovery group comprising four paired gastric cancer and adjacent gastric tissue samples, and subjected them to LC‐ESI‐MS/MS. We used a validation set comprising 129 paired gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, the associations between functioning, at least, three quarters of the cholesterol synthesis enzymes and solid cancers progression were found [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Not only overexpression and post-translational activation of enzymes correlated with pathogenic abnormalities, but also a decrease in catalytic function due to down-regulation of expression or pharmacological inhibition (SC5D, NSDHL and EBP).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the associations between functioning, at least, three quarters of the cholesterol synthesis enzymes and solid cancers progression were found [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Not only overexpression and post-translational activation of enzymes correlated with pathogenic abnormalities, but also a decrease in catalytic function due to down-regulation of expression or pharmacological inhibition (SC5D, NSDHL and EBP).…”
Section: Resultsmentioning
confidence: 99%
“…Yoon SH [ 28 ] found that NSDHL knockdown in BT-20 and MDA-MB-231 resulted in a significant decrease in their viability, colony formation, migration, and invasion abilities ( p < 0.05). Xiao Y [ 29 ] found that the over expression of NSDHL in gastric cancer (GC) was significantly correlated with local tumor invasion. Thus, exposure to 1800 MHz RF-EMR promoted cell migration by regulation of NSDHL and Dhcr21.…”
Section: Discussionmentioning
confidence: 99%
“…KIAA1363 was originally characterized as a membrane-associated serine hydrolase highly upregulated in the invasive melanoma cell line MUM-2B, the breast carcinoma cell line MDA-MB-231, and in the ovarian carcinoma cell lines OVCAR-5 and SKOV-3 [22]. Many associations or Affymetrix GeneChip array studies found elevated KIAA1363 expression and activity in pancreatic cancer [42][43][44], breast cancer [22,45], gastric cancer [46], adrenal cortical carcinoma [47], colorectal cancer [48], and chronic myeloid leukemia [49]. Since KIAA1363 expression was consistently upregulated in invasive tumors, it may represent a biomarker for early diagnosis and a potential target for the treatment of different cancers [22,44,50].…”
Section: Kiaa1363 Affects Ether Lipid Metabolism In Cancermentioning
confidence: 99%